LRPAP1 is released from activated microglia and inhibits microglial phagocytosis and amyloid beta aggregation - Reid, Kyle M.; Brown, Guy C. (Frontiers in Immunology, 2023)
Low-density lipoprotein receptor-related protein-associated protein 1 (LRPAP1), also known as receptor associated protein (RAP), is an endoplasmic reticulum (ER) chaperone and inhibitor of LDL receptor related protein 1 (LRP1) and related receptors. These receptors have dozens of physiological ligands and cell functions, but it is not known whether cells release LRPAP1 physiologically at levels that regulate these receptors and cell functions. We used mouse BV-2 and human CHME3 microglial cell lines, and found that microglia released nanomolar levels of LRPAP1 when inflammatory activated by lipopolysaccharide or when ER stressed by tunicamycin. LRPAP1 was found on the surface of live activated and non-activated microglia, and anti-LRPAP1 antibodies induced internalization. Addition of 10 nM LRPAP1 inhibited microglial phagocytosis of isolated synapses and cells, and the uptake of Ab. LRPAP1 also inhibited Ab aggregation in vitro. Thus, activated and stressed microglia release LRPAP1 levels that can inhibit phagocytosis, Ab uptake and Ab aggregation.We conclude that LRPAP1 release may regulate microglial functions and Ab pathology, and more generally that extracellular LRPAP1 may be a physiological and pathological regulator of a wide range of cell functions.